До історії Листопадового рейду 1921 р. частин Армії УНР під командуванням Ю. Тютюнника в Україну (документи ЦДАГО України про долю групи учасників рейду) - Кентій, А. (Архіви України, 2008)
Based on the investigation file (TsDAHO of Ukraine), the article highlights the issues related to preparation and implementation of November Raid (1921) of UNR Army commanded by Yu. Tiutiunnyk, to Soviet Ukraine; it also describes the relationships within the Army. The article includes unknown evidences of 4 (out of 8) UNR Army captives who were interrogated with a view of getting information related to the UNR political leadership and agents within Soviet environment.